Consensus Selection Algorithm for Automatic Primer Design System - Attanoraks*, Siriporn; Thamchaipenet, Arinthip; Piamsa-Nga, Punpiti; Soonthornphisaj, Nuanwan (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
The consensus selection is an important process in the primer design system analyzing from sets of protein or nucleotide sequences. An inappropriate consensus can cause poor primers, which can not properly bind to the DNA template. It is time-consuming for experts to select the most appropriate consensus from input alignments. Currently, there are many automatic tools to deal with the primer design problem. But all of them are not compatible and the tool for the template process has not yet been available. To improve the primer design system, this research proposes three consensus selection algorithms. The first algorithm creates the consensus using DNA backtracking from conserved region. This method gives the most appropriate consensus with the least or non-degeneracy, but can only be used with the protein sequences that had been recorded in GenBank database. The second algorithm groups the consensus by conserved regions to calculating consensus score from the number of degeneracy and consensus length. This algorithm gives high degeneracy consensus with the longest length. The third algorithm groups the consensus islands from conserved regions by the connection of low degeneracy characters and calculating consensus score. This algorithm gives high specific consensus and can be sued with unknown protein sequences. We integrate these algorithms with the alignments and primer design process in order to create the automatic primer design system that can deal with large protein sequences for designing both PCR primers and probes. Our system includes decision support and primer analysis tools. The pre-version of this automatic primer design system (KUPDS) is available at: http://kupds.com Keywords: Primer Design, Consensus, Alignment, PCR, Bioinformatics. Corresponding author: E-mail: fscinws@ku.ac.th